2004
DOI: 10.1590/s0103-20032004000100009
|View full text |Cite
|
Sign up to set email alerts
|

Nível tecnológico e rentabilidade de produção de mel de abelha (Apis mellifera) no Ceará

Abstract: O presente estudo procurou analisar a apicultura no Estado do Ceará, enfocando a produção de mel de abelhas (Apis mellifera) nos principais municípios produtores do Estado, mais precisamente fazendo uma análise do nível tecnológico empregado na produção, bem como avaliando a rentabilidade da atividade. A pesquisa se realizou através de coleta de dados primários por meio de entrevistas diretas com os produtores nos municípios de Mombaça, Pacajús e Chorozinho, no mês de outubro de 2002. Para avaliação do nível t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
25

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 0 publications
1
12
0
25
Order By: Relevance
“…With regard to cost items and profitability of the process of honey production in Brazil, Feitosa et al (2004), found that honey production is very profitable, which coincides with the present study. Meanwhile, the results of CREEBBA (2005) presents evidence of the crisis of profitability of small and medium producers of Argentina; while Engler et al (2008), observed for Chile that the profit margin in beekeeping is minimal, especially for those traditional production systems.…”
Section: Conceptosupporting
confidence: 91%
“…With regard to cost items and profitability of the process of honey production in Brazil, Feitosa et al (2004), found that honey production is very profitable, which coincides with the present study. Meanwhile, the results of CREEBBA (2005) presents evidence of the crisis of profitability of small and medium producers of Argentina; while Engler et al (2008), observed for Chile that the profit margin in beekeeping is minimal, especially for those traditional production systems.…”
Section: Conceptosupporting
confidence: 91%
“…Brazil went from importer to exporter of honey (FARGS 2008), which shows that there is a potential for development of beekeeping and for the growth on the honey market. For the producer that starts in apiculture (honey bees) or meliponiculture (stingless bees), beekeeping is a family activity, informal, and even secondary, an alternative occupation and income, with low initial cost and easy maintenance (Freitas et al 2004). But increasing competitiveness in the honey chain depends on the increasing associative capacity of beekeepers and depends on better coordination among them (Lengler and Rathmann 2006).…”
Section: Initiatives In Beekeeping At Embrapa Temperate Agriculturementioning
confidence: 99%
“…Este crescimento demonstra a importância em se realizar uma análise de viabilidade econômica para a produção de mel na região, a partir do qual será possível identificar os retornos econômicos que esta atividade pode trazer para os investidores. Na literatura há trabalhos que constataram a viabilidade dessa atividade, porém os estudos foram focados em regiões distintas e que não representam a região de Botucatu, como por exemplo, no estado do Ceará (Freitas et al, 2004), Pantanal MatoGrossense (Barros;Reis, 2004), Planalto Norte de Santa Catarina (Kreuz et al, 2008), norte do estado de São Paulo (Sabbag;Nicodemo, 2011) e oeste do Paraná (Paschoal;Paschoal, 2013).…”
Section: Introductionunclassified